Pengaruh Risiko Kredit terhadap Profitabilitas Pada PT Bank Rakyat Indonesia Tbk Periode 2012-2019 - Tia Setiani; Wahyu Deny Widiastuti (JAMER : Jurnal Akuntansi Merdeka, 2022)
Banking in improving financial performance by using profitability. Profitability is the bank's ability to earn profits over several periods. So that banks always try to avoid risks that occur, such as risks in providing credit. The risks that occur will cause losses for the bank, one of which will reduce the value of profitability. The method used in this research is quantitative method using secondary data sources, which is done by using the method of document collection and literature study. The population in this study is financial reports. The sample used is using purposive sampling technique. The analytical tools used in this research include simple linear regression analysis, product moment correlation analysis, determination coefficient analysis and t test. The results of statistical calculations using SPSS Version 26 concluded that there is a negative and significant influence between Credit Risk and Profitability at PT. Bank Rakyat Indonesia Tbk. The results of the t test for the credit risk of the significance value of 0.010 < 0.05 have significant effect between the credit risk to profitability